The domestic market for small-scale chainsaw milling in Cameroon: present situation, opportunities and challenges - Cerutti, P.O.; Lescuyer, G. (Center for International Forestry Research, 2011)
In 1994 Cameroon adopted a new forest law that focussed on the large-scale, export-oriented industrial forest sector while timber produced through small-scale logging for the domestic market was ignored, even in official statistics, and is generally produced without a valid permit. As Cameroon prepares to implement the Voluntary Partnership Agreement (VPA) it recently signed with the European Union, promising a legal framework for all national timber production, this occasional paper presents a quantitative and qualitative evaluation of the country’s domestic timber market. By adding our estimates for small-scale production of sawn wood sold on the domestic market to national statistics, total national production would amount to about 4.3 million cubic metres per year, in other words close to double the official figure for Cameroonian timber production. Our research also found that the domestic market is profitable for thousands of Cameroonians. Its informal structure, however, contributes to maintaining a huge, inescapable payment system run by State agents to launder the timber sold on local markets, informal transactions that are worth about 6 billion F CFA each year. The paper concludes with technical options to improve market operating conditions. These options may prove ineffective unless they are accompanied by determined efforts to fight the corruption that permeates the industry.